The Influence of Attitude, Subjective Norm, and Perceived Behavioural Control Toward Snack Consumer Behaviour in Halal Labeling in Yogyakarta - Ayu Afsari; Any Suryantini; Jangkung Handoyo Mulyo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Halal label was not only related to substances forbidden for a particular religion, but was also associated with many other important things. The talk about halal label issue also meant a talk about health and hygiene. This research aimed to determine the learning level of consumer of the concept of halal-labeled snack; to know how to influence learning, attitudes, subjective norms, perceived behavioural control, and the prices on consumer behaviour of packaged halal-labeled snack, either partially or simultaneously. The effect was determined using a multiple linear regression analysis. Data were collected through compiled structured questionnaires based on certain indicators addressed to 100 respondents. The sampling technique used in this study was a convenience sampling technique, where the sample was selected from members of the population willing to become respondents. The choice of location was determined intentionally (purposive). Attitude scale used was Likert scale, and scale variable used was interval scale. The results showed that the consumer learning level on a basic concept of halal contained in a halal label was very high. This was proven with the results of the interpretation of a score interval, i.e. 88.12%. Consumer behaviour towards snacks in packaging labeled halal simultaneously was influenced by learning, attitudes, subjective norms, perceived behavioural control, and price, while attitude and price influenced partially.